2023
DOI: 10.1101/2023.10.09.561274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA cap-binding protein eIF4E1 is a novel regulator ofToxoplasma gondiilatency

Michael J. Holmes,
Matheus S. Bastos,
Vishakha Dey
et al.

Abstract: The protozoan parasiteToxoplasma gondiicauses serious opportunistic disease due to its ability to persist in patients as latent tissue cysts. The molecular mechanisms coordinating conversion between proliferative parasites (tachyzoites) and dormant cysts (bradyzoites) are not fully understood. We previously showed that phosphorylation of eIF2α accompanies bradyzoite formation, suggesting that this clinically relevant process involves regulation of mRNA translation. In this study, we investigated the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Another possibility, given the decreased abundance of many proteins involved in translation in the ABCB7 mutant, is that a block in translational could induce the parasite to begin differentiation. Previous studies have shown translational control to be an important aspect of initiating differentiation (61)(62)(63)(64)(65). More work needs to be done to understand how stress and metabolic deficiencies influence a parasite's decision to initiate conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, given the decreased abundance of many proteins involved in translation in the ABCB7 mutant, is that a block in translational could induce the parasite to begin differentiation. Previous studies have shown translational control to be an important aspect of initiating differentiation (61)(62)(63)(64)(65). More work needs to be done to understand how stress and metabolic deficiencies influence a parasite's decision to initiate conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we wanted to test whether in vitro-generated capped RNA could be recognized by eIF4E-like protein and productively translated into protein in Toxoplasma. BLASTP search using Plasmodium 50 and human 51 eIF4E revealed three eIF4E-like homologues (TGME49_223410, TGME49_315150, and TGME49_312560) in T. gondii genome 52 . Of these three homologue, TGME49_223410 showed highest amino acid similarity, including conserved residues required for m 7 G interaction with Plasmodium (e score: 1e-69) and human protein (e score: 1e-14) (Supplementary Fig.…”
Section: Cap-dependent Translation In Vitromentioning
confidence: 99%
“…The phosphorylation of eIF2α has been demonstrated as crucial for stage conversions in Leishmania 27 , Plasmodium 28,29 , Trypanosoma 30 , and T. gondii 31 . Recently, it has also been reported that the absence of eIF4E1, a key player in the cap recognition step of translation initiation, can trigger T. gondii differentiation 32 . With eIF4E1’s function in differentiation working in parallel with that of eIF2α, the translation-directed regulatory landscape of differentiation is likely more complex than previously acknowledged.…”
Section: Introductionmentioning
confidence: 99%